Answer:
x =7
Explanation:
Remark
- A geometric sequence always has terms that are separated by a common ratio. For example 3 9 27 81 243 ....
- Each term is multiplied by a common number and the term before it. In this case the common term is 3.
- To get the next term after 9, you multiply 9 by 3.
- To get the common ratio divide the second term by the first and then the third term by the second
Equation
(x + 2)/(x - 4) = (3x + 6)/ (x + 2)
Solution
I would begin this problem by taking out the common factor on the top right term. You'll see why in a second.
(x + 2)/(x - 4) = 3(x + 2)/ (x + 2) Notice the two binomials on the right cancel.
- (x + 2)/(x - 4) = 3/1 Cross multiply
- (x + 2)*1 = 3*(x - 4) Remove the brackets on the right.
- x + 2 = 3x - 12 Add 12 on both sides.
- x + 2 + 12 = 3x - 12 + 12 Simplify
- x + 14 = 3x Subtract x from both sides
- 14 = 3x - x
- 2x = 14 Divide by 2
- x = 14/2
- x = 7